EKSISTENSI AGAMA SIKH DI JABODETABEK - Zainal Abidin (Jurnal Dialog, 2015)
This study investigates the existence aspect of Sikh followers in Jabodetabek (Jakarta, Bogor, Depok, Tangerang and Bekasi) regions. It aims to provide data and information regarding the government services to all religious communities including minorities, such as Sikh. The existence aspects under study include the short history, the basic teachings, rituals, institutions, and social interaction. This study utilizes qualitative research using postcolonial and subaltern perspective from Gayatri C Spivak’s view. Theologically, Sikh believes in monotheism that was mentioned by Waheguru and Guru Nanank (1469-1539). Sikh has a holy book named Guru Granth Sahib. Sikh temple is called Gurdwara or the “gateway to the Guru”. Sikh followers came to Indonesia from Amritsar, Punjab, India, (now Pakistan territory) through Aceh, North Sumatra and Jakarta. Sikh followers are managed under the Hindu Guidance Directorate. They do not have a national organization that accommodates Sikh community in Indonesia. It can be concluded that the existence of the Sikh in Jabodetabek area is somewhat subaltern.